DIPLOMASI EKONOMI TIONGKOK DENGAN NEGARA-NEGARA SUNGAI MEKONG MELALUI PROGRAM ONE BELT ONE ROAD TAHUN 2013-2021 - Filianstya Hariono; Risdiyanti Risdiyanti; Maria Indira Aryani (Universitas Halu Oleo, 2022)
One Belt One Road, widely knowns as OBOR is an ambitious program initiated by China in 2013 with the aim of increasing the economic growth of China and its partner countries in Asian, African, and European regions. One of the sub-regions in Asia that has always been the main focus of OBOR is the Mekong River Region, namely Myanmar, Thailand, Laos, Vietnam, and Cambodia, having geographical proximity to China. The implementation of the program is marked by the existence of infrastructure development for the creation of special economic zones. This research is aimed at explaining the OBOR program, by analyzing the role of economic diplomacy in achieving China's national interests through OBOR. The relations factor and the role of the state as the largest foreign direct investment are the most prominent factors in the success of China's economic diplomacy through OBOR. The research method used in this article is qualitative with literature study data collection techniques. This research is limited from 2013, when OBOR was first initiated, to 2021, when the United States’ Build Back Better World Initiatives emerged